To be or not to be - Heymann, Werner Richard 1896-1961 (The Criterion collection, 2013)
As nervy as it is hilarious, a masterpiece from Ernst Lubitsch, To Be Or Not To Be; is a Hollywood film of the boldest black humor, which went into production soon after the U.S. entered World War II. Lubitsch manages to brilliantly balance political satire, romance, slapstick, and urgent wartime suspense in a comic high-wire act that has never been equaled